Expression of Retinal G Protein-Coupled Receptor, a Member of the Opsin Family, in Human Skin Cells and Its Mediation of the Cellular Functions of Keratinocytes - Gu, Yangguang; Wang, Yu; Lan, Yinghua; Feng, Jianglong; Zeng, Wen; Zhang, Wei; Lu, Hongguang (Frontiers in Cell and Developmental Biology, 2022)
Photoreceptive proteins play critical physiological roles in human skin cells. Retinal photo isomerase is a G protein-coupled receptor (RGR) in human retina but its expression and cellular functions in human skin cells remain unclear. Objectives herein, we aim to detect the expression of RGR in various skin cells and to study its regulation on cellular functions of keratinocytes. Methods The expression, distribution and subcellular location of RGR in normal human epidermal keratinocytes and cells from pathological conditions including psoriasis, seborrheic keratosis and squamous cell carcinoma were determined by microscopic tools (immunohistochemical staining, immunofluorescence staining, immuno-electron microscope) and Western blot (WB). The protein levels of RGR between primary human melanocytes, keratinocytes, and fibroblasts isolated from neonatal foreskin were measured by WB analysis. The expression and subcellular localization of RGR in these cells were detected by immunofluorescent staining under fluorescent microscope and laser scanning confocal microscope. In addition, the levels of RGR expression in normal keratinocytes exposed to UVA or UVR in the presence or absence of all-trans retinal were measured by WB. Furthermore, RGR’s effects on human keratinocytes’ functions including proliferation, migration and apoptosis were evaluated by CCK-8, Wound healing and Transwell assays, through reducing RGR mRNA levels in keratinocytes using small RNA Interference technology. Results RGR are mainly located in the epidermal basal and spinous layers, and in the skin appendages. Its expression is increased in the lesions of psoriasis, seborrheic keratosis and squamous cell carcinoma. Confocal microscopic data showed that RGR is located in the cell membrane of keratinocytes, melanocytes and fibroblasts. In addition, the expression level of RGR is higher in keratinocytes (as compared to melanocytes and fibroblasts), where RGR is detected in the cell nucleus by nuclear plasma separation technique. Notably, knockdown of RGR (by RNAi-RGR) in keratinocytes led to the inhibition of cell proliferation and migration, and thereby augmented cell apoptosis. Conclusions This is the first study showing the presence of RGR in the human skin. Moreover, our findings indicate that RGR may play a critical role in the physiological function of epidermal keratinocytes.